Pengembangan E-Modul Berbasis Inkuiri untuk Meningkatkan Kemampuan HOTS Siswa Sekolah Dasar di Kota Blitar - Anam, M. Saiful; Koeshandayanto , Supriyono; Mashfufah, Aynin; Maulana, Abdur Rofik (BRILIANT: Jurnal Riset dan Konseptual, 2025)
This research aims to develop an inquiry-based e-module to improve the ability of HOTS on electrical materials to change the face of the world in grade VI elementary school. The development method used is the Lee and Owen method, which includes the stages of assessment / analysis (Needs assessment and Front-end analysis), Design, Development, Implementation, and Evaluation. Qualitative and quantitative approaches are used in analyzing data, using validation instruments, teacher response questionnaires, student response questionnaires, and HOTS ability tests as data collection tools. The results of data analysis showed that inquiry-based e-modules on electrical materials changing the face of the world had a feasibility rate of 86%, with the category "very practical". Student assessments also confirm the validity, effectiveness, and practicality of the e-module. The implication of the results of this study is a significant contribution in improving the HOTS of grade VI students at the UPT satuan Pendidikan SDN Klampok Kota Blitar. However, for the development of subsequent e-modules, it is recommended to continue to involve input from experts and teachers, and consider adjustments that may be needed based on student responses, in order to ensure the sustainability and successful use of these e-modules in improving HOTS.